Awareness of Polycystic Ovarian Syndrome (PCOS) in young adult female university students from Lahore Pakistan - Muhammad Waseem Riaz; Shiza Ashraf; Muhammad Saad Azam; Nauman Ismat Butt; Barak Waris; Muhammad Sohail Ajmal Ghoauri (Journal of Current Health Sciences, 2026)
Polycystic ovary syndrome (PCOS) is a prevalent endocrine disorder among women of reproductive age, associated with menstrual irregularities, infertility, and long-term metabolic risks. Despite its common occurrence, awareness and understanding of PCOS remain inadequate among young women. This study aimed to assess the level of awareness, common misconceptions, and sources of information about PCOS among young adult female university students. A descriptive cross-sectional study was conducted at Superior University, Lahore, Pakistan. One hundred female students aged 18–25 years were recruited through non-probability consecutive sampling after obtaining informed consent. Participants with a current or past diagnosis of PCOS were excluded. Data on demographics, knowledge and perceptions of PCOS were collected using a structured self-administered questionnaire and analyzed using SPSS version 23. Descriptive statistics were used to summarize the findings. All participants (100%) had heard of PCOS. Knowledge accuracy was limited: 71% recognized irregular menstrual cycles as a common symptom, only 47% correctly identified PCOS as a hormonal disorder, and 38% considered it treatable. Emotional and perception responses were predominantly worry (67%) and fear (24%), with 57% associating PCOS with infertility. The majority perceived lifestyle modification (54%) as the preferred treatment. Main sources of awareness were educational settings (46%) and TV/social media (30%). Notably, just over half (52%) indicated they would seek medical consultation, highlighting a key behavioral implication for campus health education. While awareness of PCOS was high, misconceptions about its hormonal basis and management persist, and emotional responses indicate considerable concern among students. Targeted health education programs are needed to improve knowledge, address misconceptions, and promote timely help-seeking behaviors in university settings.